2019
DOI: 10.1029/2019gl084357
|View full text |Cite
|
Sign up to set email alerts
|

Deep Low‐Frequency Earthquakes Beneath the Hakone Volcano, Central Japan, and their Relation to Volcanic Activity

Abstract: Deep low‐frequency earthquakes (DLFEs) are ubiquitous seismic activities in the deep parts of volcanoes. Owing to the low signal‐to‐noise ratio, the seismic activities of DLFEs have not been characterized in detail; particularly, the linkage between DLFEs and shallow volcanic activity has not been understood sufficiently. In this study, numerous DLFEs have been successfully detected beneath the Hakone volcano, central Japan, by cross‐correlating a template to the continuous seismic signals. The resulting seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Our GNSS analysis detected the inflation of a deep spherical source in late March 2015, well before the onset of the seismic swarm activity in late April. It is interesting to note that a deep low-frequency event (DLF) began at approximately the same time as the inflation (Yukutake and Abe 2018;Mannen et al 2018). However, the DLF occurred at 15-30 km depth, much deeper than the deep spherical source at 5-6 km depth (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our GNSS analysis detected the inflation of a deep spherical source in late March 2015, well before the onset of the seismic swarm activity in late April. It is interesting to note that a deep low-frequency event (DLF) began at approximately the same time as the inflation (Yukutake and Abe 2018;Mannen et al 2018). However, the DLF occurred at 15-30 km depth, much deeper than the deep spherical source at 5-6 km depth (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3). Yukutake and Abe (2018) hypothesized that the DLF event may be due to an increase in magmatic fluid pressure. This suggests that such fluid may have migrated to shallower depths, potentially generating inflation of the deep spherical source discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Geophysical Research: Solid Earth with the supply of magmatic fluids from deep zone (Yukutake et al, 2019), occur in this moderate-attenuation area (Figures 9f and 10b).…”
Section: 1029/2020jb020341mentioning
confidence: 95%
“…At approximately 20 km beneath the northern caldera rim of the volcano, DLFs occur sporadically. Since many of the DLF swarm events were followed by in ation of the edi ce and shallow volcano-tectonic earthquake swarms, DLFs are interpreted as a signal indicating migration of magmatic uid (Yukutake et al 2015(Yukutake et al , 2019. A seismic tomography study revealed velocity structure beneath Hakone volcano and showed that the volcano has an active magma-hydrothermal system (Yukutake et al 2015).…”
Section: Subsurface Structure Of Hakone Volcanomentioning
confidence: 99%
“…The 2001 unrest accompanied an earthquake swarm, and deep and shallow in ation as observed by Global Navigation Satellite System (GNSS) and a tiltmeter network, and culminated with a blowout of a steam production well (SPW) in Owakudani (500 m deep). Since the 2001 unrest, major volcanic unrest episodes comprising earthquake swarms, deep in ation detected by a GNSS network, and deep low frequency events (DLF) were observed in 2006, 2008-2009and 2013(Harada et al 2018Yukutake et al 2019). In terms of seismicity, these events can be intensive as historical unrest episodes before 1960.…”
Section: Introductionmentioning
confidence: 99%